080. Clinical Complete Resolution of Breast Cancer Achieved After Four Cycles of Chemotherapy: A Case Report of A 44-Year-Old Woman - Napitupulu, Aretti Sari; Siregar, Kamal Basri (JBN (Jurnal Bedah Nasional), 2024)
Background : Breast cancer is a major cause of cancer-related deaths in women, with early detection critical for improving outcomes. In resource-limited settings, delayed diagnosis is common, leading to more advanced disease at presentation. This case report details a 44-year-old woman who achieved clinical complete resolution of her breast cancer after four cycles of chemotherapy. Case: The patient first noticed a marble-sized lump in the upper lateral quadrant of her left breast in August 2023. Despite the growing size of the mass, which increased to 5 cm over four months and became immobile, she delayed seeking medical care. Upon presentation, a biopsy confirmed a diagnosis of breast cancer. The patient was started on chemotherapy, receiving four cycles as a neoadjuvant treatment. Post-treatment examinations revealed a clincal complete resolution of the tumor, and she was subsequently scheduled for a mastectomy to remove any remaining disease and prevent recurrence. The post operative histopathology result; some viable tumor cells are still present in the left breast specimen and Sinus histiocytosis is present (no tumor cells are found) in all the lymph nodes examined. Conclusion: The clinical complete resolution observed in this patient following chemotherapy underscores its effectiveness in breast cancer treatment. Even though histopathological stated that there was minimal leftover cancer cells detected, which can be further treated with adjuvant chemoterapy. This case supports the need for increased awareness, early diagnosis, and access to chemotherapy for improving breast cancer outcomes.